(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
This paper tries to analyze the latest trend in democratization gained less attention in academic works. In Industrial period, democratization was lead in the direction of secularization, however, in societies which are postmodern or undergoing recent democratization, democracy is gaining more feminist fashion. Genderization of politics or feminist interpretation of democracy is the cornerstone of such analytical attempt. Despite, structural transformation of democracy in advanced democracies, feminist ideas are standing at the core of democracy.